CbRCI35, a Cold Responsive Peroxidase from Capsella bursa-pastoris Regulates Reactive Oxygen Species Homeostasis and Enhances Cold Tolerance in Tobacco - Zhou, Mingqi; Li, Weiwei; Zheng, Ye; Lin, Ping; Yao, Xiaohua; Lin, Juan (Frontiers in Plant Science, 2016)
Low temperature affects gene regulatory networks and alters cellular metabolism to inhibit plant growth. Peroxidases are widely distributed in plants and play a large role in adjusting and controlling reactive oxygen species (ROS) homeostasis in response to abiotic stresses such as low temperature. The Rare Cold-Inducible 35 gene from Capsella bursa-pastoris (CbRCI35) belongs to the type III peroxidase family and has been reported to be a cold responsive gene in plants. Here we performed an expressional characterization of CbRCI35 under cold and ionic liquid treatments. The promoter of CbRCI35 was also cloned and its activity was examined using the GUS reporter system. CbRCI35 protein was localized in the cytoplasm according to sequence prediction and GFP fusion assay. Heterologous expression tests revealed that CbRCI35 conferred enhanced resistance to low temperature and activated endogenous cold responsive signaling in tobacco. Furthermore, in the normal condition the ROS accumulation was moderately enhanced while after chilling exposure superoxide dismutase (SOD) activity was increased in CbRCI53 transgenic plants. The ROS metabolism related genes expression was altered accordingly. We conclude that CbRCI35 modulates ROS homeostasis and contributes to cold tolerance in plants.